(untitled) (Contemporary Mathematics, 2024)
This article presents a contribution to modelling of rainfall hazards in a stochastic framework. The independence of the realizations of a process conditionally on the latent random effect, which also allowing us to calculate the likelihood of the observed annual maxima. We also showed the predominance of the moment estimator over the Hill estimator. Furthernore, we used a stochastic model to provide a temporal framework for modeling extreme events, as well as the evolution of extreme rainfall in west Africa from 2019 to 2169, which shows a significant decrease over the entire range of the different stations.